1998
DOI: 10.1002/lt.500040208
|View full text |Cite
|
Sign up to set email alerts
|

Is vaccination against hepatitis B infection indicated in patients waiting for or after orthotopic liver transplantation?

Abstract: It is a common practice to immunize patients against hepatitis B infection while they are waiting for liver transplantation, but the efficacy of this practice is unclear. This is a retrospective analysis of the antibody response to 20 g of a recombinant hepatitis B vaccine in patients waiting for and after liver transplantation. The response to vaccination was measured 1-3 months after completion of the vaccination series. The risk of acquiring hepatitis B virus after liver transplant was determined by reviewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
86
0
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 25 publications
2
86
0
5
Order By: Relevance
“…21 Similarly, in adult patients with cholestatic liver disease, a significantly better response to vaccination was seen as compared to noncholestatic forms of liver disease (43% vs. 7%). 22 The better immunogenicity of the adjuvanted HB-AS04 vaccine observed in this study confirms previous results in healthy subjects 16,17 as well as in prehemodialysis and hemodialysis patients. 23 Long-term protection after the HB-AS04 booster dose has not been evaluated in this study.…”
Section: Discussionsupporting
confidence: 91%
“…21 Similarly, in adult patients with cholestatic liver disease, a significantly better response to vaccination was seen as compared to noncholestatic forms of liver disease (43% vs. 7%). 22 The better immunogenicity of the adjuvanted HB-AS04 vaccine observed in this study confirms previous results in healthy subjects 16,17 as well as in prehemodialysis and hemodialysis patients. 23 Long-term protection after the HB-AS04 booster dose has not been evaluated in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Confronted with the above-mentioned literature, [23][24][25][26] the satisfactory rate of seroconversion reached in our series can be accounted for by considering first the fact that we administered a double dose schedule of three 40-µg doses and additional complete courses of vaccination whenever the first one was ineffective, and second the long time elapsed after liver transplantation, which allowed a marked tapering of the immunosuppressive drugs. The poor rate of seroconversion obtained in those patients who had withdrawn steroid treatment most recently backs up the latter hypothesis.…”
Section: Discussionmentioning
confidence: 79%
“…Before long-term HBIG became the established HBV prophylactic treatment, HBV vaccine was usually administered perioperatively, together with short-term passive immunoprophylaxis, and continued thereafter in the postoperative phase 3,21,22 although with only anecdotal effectiveness. 5 On the other hand, reports on HBV vaccination in non-HBV adult liver transplant recipients have shown very low rates of seroconversion, [23][24][25] probably because of the fact that vaccination was administered before transplantation or immediately after. Our study attempts to induce anti-HBs seroconversion as a means to discontinue indefinite HBIG treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is also clinically well recognized that cirrhotic patients have suboptimal responses to vaccines such as the hepatitis B vaccine. In several series, HBV vaccinations in cirrhotic patients yielded response rates from 13 to 54% [28,29] with minimal improvement by doubling the dose [30], much poorer than the results in noncirrhotic patients. In a study of conjugated pneumococcal vaccine in liver disease, cirrhotic patients showed transient exaggerated early IgM and IgA production but impaired total IgG response suggesting defective IgG class-switching among cirrhotic patients relative to healthy donors [31].…”
Section: Discussionmentioning
confidence: 99%